Examining the Competitiveness of Fish Products on the Market - Mihály, Tamás; Soós, Mihály (International Journal of Engineering and Management Sciences, 2022)
Fish and fishery products are one of the key ingredients in human nutrition and are therefore outstanding in terms of both production and trade. Different processed fish products are available in many countries around the world due to globalization and a fast supply chain. In our study, we examined the market for fish and fishery products using secondary data collection. The data were collected several years ago from the databases of FAO, EUROSTAT, COMTRADE and KSH The comparative advantages or disadvantages of international trade were determined with the help of the RCA index for the role of Hungary and the EU in the world in the case of different categories of fish products. The aim of our research is to compare the fish products of different processing in Hungary and in the EU compared to the international situation, paying special attention to the main exporting and importing countries. Based on the secondary research the study has a detailed the specificities of trade, the trends observed in recent years and the competitiveness of fish products in Hungary and the Member States of the European Union and effect relationships behind the RCA-index results.